2010
DOI: 10.1007/s10517-010-1072-3
|View full text |Cite
|
Sign up to set email alerts
|

The Expression and DNA-Binding Activity of NF-κB Nuclear Transcription Factor in the Tumors of Patients with Breast Cancer

Abstract: The content and DNA-binding activity of NF-κB nuclear transcription factor subunit p65 (NF-κBp65) were evaluated by quantitative enzyme immunoassay in tumors and histologically intact tissues of 119 patients with breast cancer. DNA-binding activity of NF-κBp65 in the tumors was higher than in adjacent tissue in 97% cases. This elevation was paralleled by an increase in total protein content in the majority of cases. No significant relationship of the parameter with the disease stage, tumor size and histology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…As illustrated in Figure 1A, NF-κB was revealed as one of the most distinctive pathways in basal-like tumors. This is consistent with previous reports that sustained NF-κB activation exists mostly in human BLBC cell lines (23, 24) and ER-negative breast cancer (25) with its highest activity found in triple-negative tumors (26). NF-κB activity was also found to be essential for the proliferation and survival of BLBC cells (23).…”
Section: Resultssupporting
confidence: 93%
“…As illustrated in Figure 1A, NF-κB was revealed as one of the most distinctive pathways in basal-like tumors. This is consistent with previous reports that sustained NF-κB activation exists mostly in human BLBC cell lines (23, 24) and ER-negative breast cancer (25) with its highest activity found in triple-negative tumors (26). NF-κB activity was also found to be essential for the proliferation and survival of BLBC cells (23).…”
Section: Resultssupporting
confidence: 93%
“…The transcription of MMPs is regulated by upstream sequences, including motifs corresponding to NF-κB. It is a transcription factor shown to be significantly increased in TNBC tumors, which is consistent with the aggressiveness of these tumors [ 35 ]. Our present results demonstrated that DATS inhibited NF-κB transcriptional activity.…”
Section: Discussionmentioning
confidence: 88%
“…There are many contradictions in the results of such studies associated with absence of a standard method of determining the NF-κB activation, and the differences in interpretation of results obtained by the same method. However, most results suggest that NF-κB is activated mainly in ER-negative andHer2/neu-positive tumors [15,[18][19][20][21][22]. These tumors usually have a high proliferative index and Grade and form a group with the worst prognosis and high chemoresistance.…”
Section: Introductionmentioning
confidence: 99%